Graphene Oxide: A Key Solution for Future: Recent Achievements as A New Adsorbent for Water Treatment Applications: Review - Salih, Watheq K.; Mohammed, Sawsan A. M.; Abdulmajeed, Basma A. (Iraqi Journal of Science, 2023)
Polluted water has been considered a critical issue nowadays, threatening the environment and lives of living creatures. Because of technological and industrial advancements, as well as increased social activities of humans in various countries, pollution sources have multiplied. To reduce the impact of this problem, many techniques have been developed in order to reach zero discharge pollution. In the last decade, graphene oxide (GO) - a member of the graphene nanomaterials family, has been the focus of many research efforts in the water treatment sector because of its extraordinary properties. This review highlights the research efforts conducted to investigate GO as a novel adsorbent for water treatment applications and recent fulfilments in the last 3 years. The synthesis techniques, properties, and efficiency of this material in water treatment will be explained. All results confirm the future role of GO as an efficient absorbent to solve wastewater purification challenges, but the big challenge is to reduce time and simplify the complicated extent of synthesis stages, besides reducing the high cost of production methods. According to the review, Iraqi researchers’ efforts to use this nanomaterial in water purification are still in their early stages.